Understanding advanced materials for solar panels: interplay of composition, structure and optoelectronic properties in new metal-halide semiconductors - Buizza, L (2021)
Interest in metal-halide semiconductors has risen rapidly over the past decade, notably due to the success of lead-halide perovskites in solar cells, whose efficiencies have risen to rival those of best-in-class commercial materials. Alongside this improvement in device-based performance, a detailed understanding of the underlying optoelectronic properties of such materials has developed, focusing on the most successful lead-halide perovskite materials. This thesis provides insights into how the composition and structure of such materials influence their optoelectronic properties, focusing especially on charge-carrier dynamics and transport. The materials investigated for this thesis all move beyond conventional lead-halide perovskites, pushing the boundaries of materials discovery and thus making a clear understanding of their fundamental properties crucial to their successful deployment in optoelectronic and energy applications.